From eco-friendly to fashionable: An investigation into Chinese consumers' demand for paper handbags in all dimensions - Haifei Ge; Jaewook Shin (Sustainable Futures)
In recent years, there has been a notable shift in consumer and business attitudes towards sustainable environmental protection. This has led to an increased demand for products that combine fashion and environmental responsibility, with paper handbags emerging as a popular choice in this regard. The objective of this study is to analyse the purchasing demand of Chinese consumers for environmentally friendly and fashionable paper handbags, with a view to providing a reference for companies' product design and marketing strategies. This study employs a combination of the KJ method and the Delphi method to construct 30 demand indicators for environmentally friendly and fashionable paper handbags, organised into seven dimensions. The four-quadrant analysis method of the KANO model is then used to rank and accurately classify these indicators, based on the advantage and disadvantage coefficients. The study demonstrates that the demand for environmentally friendly and fashionable paper handbags among Chinese consumers tends to be grouped and concentrated, with a clear division of demand. The findings of this study offer a foundation for businesses to categorise market demand and refine the design of environmentally friendly and fashionable paper handbags, thereby enhancing market competitiveness and providing an analytical framework for the development of other sustainable products.